Citations and Citation Metrics in a Serial Assessment Using Master's Theses. Issue 3 (3rd July 2018) - Timms, Geoffrey P.
Abstract: We analyzed serial citations in 72 marine biology master's theses as well as the ranking data of aquatic science serials from six global serial citation metrics, to assess serial use by marine biology graduate students from two perspectives. From 1, 035 unique serials, a core of 123 titles was identified and evaluated for access. Citation ages averaged 13.5 years, with 27% of serial citations dated prior to 1996. Students cited serials from disciplines beyond marine biology, demonstrating broad title dispersion compared to several other studies. Recommendations are offered for future investigation to develop a stronger understanding of graduate students' use of the library's serial collection.